Transcriptomic analyses of cacao cell suspensions in light and dark provide target genes for controlled flavonoid production (2018)
ABSTRACT: Catechins, including catechin (C) and epicatechin (E), are the main type of favonoids in cacao seeds. They play important roles in plant defense and have been associated with human health benefts. Although favonoid biosynthesis has been extensively studied using in vitro and in vivo models, the regulatory mechanisms controlling their accumulation under light/dark conditions remain poorly understood. To identify diferences in favonoid biosynthesis (particularly catechins) under diferent light treatments, we used cacao cell suspensions exposed to white-blue light and darkness during 14 days. RNA-Seq was applied to evaluate diferential gene expression. Our results indicate that light can efectively regulate favonoid profles, inducing a faster accumulation of phenolic compounds and shifting E/C ratios, in particular as a response to switching from white to blue light. The results demonstrated that HY5, MYB12, ANR and LAR were diferentially regulated under light/dark conditions and could be targeted by overexpression aiming to improve catechin synthesis in cell cultures. In conclusion, our RNA-Seq analysis of cacao cells cultured under diferent light conditions provides a platform to dissect key aspects into the genetic regulatory network of favonoids. These light- responsive candidate genes can be used further to modulate the favonoid production in in vitro systems with value-added characteristics.